(untitled) (Research, Society and Development, 2021)
Among the tubers available in the Amazon, Dioscorea bulbifera has stood out as a source of nutrients beneficial for human health. However, this species is not economically exploited and there are few records reporting the technological utilization for the elaboration of food products. The objective of this work was to elaborate D. bulbifera chips by different thermal processing methods. The tubers were harvested in a household establishment located in the east zone of the city of Manaus-AM. To prepare the chips, the tubers were sliced with the help of a stainless knife in sizes of 2 mm thick and submitted to baking in an oven at 180 °C for 30 minutes and frying in soybean oil at 180 °C for 2 minutes. In the chips were determined the centesimal composition (moisture, ashes, lipids, fibers, proteins, carbohydrates and caloric value), physicochemical characteristics (pH and acidity) and microbiological quality (Escherichia coli and Salmonella sp.). Processing influenced the nutritional composition and physicochemical properties of the chips. Significant values of moisture (26.47%), ash (2.23%) and protein (4.12%) were verified in the baked chips. Fried samples had significant contents of lipids (3.47%), fibers (5.01%), carbohydrates (81.25%) and energetic value (371.26 kcal/100 g). The acidity values of the baked and fried samples were 0.25% and 0.27%, respectively. There was no difference between the pH values of the chips. E. coli growth and the presence of Salmonella sp. were not observed in the samples. Dioscorea bulbifera from the Amazon constitutes an alternative and innovative source for chip production.